Emission accounting and drivers in 2004 EU accession countries. (15th May 2022) - Xiao, Lin; Guan, Yuru; Guo, Yaqin; Xue, Rui; Li, Jiashuo; Shan, Yuli
Highlights: CO2 emission accounts 2005–2017 of 2004 EU accession members. The ten members are hampering the EU's goal of achieving carbon neutrality. Potential roadmaps towards carbon neutrality by designing 33 scenarios. Abstract: The ten countries that joined the European Union (EU) in 2004 (Cyprus, Czechia, Estonia, Hungary, Lithuania, Latvia, Malta, Poland, Slovakia, and Slovenia) have experienced faster economic growth and slower declines in energy consumption than traditional EU members. As designing of low-carbon policies requires accurate CO2 emission accounting, this study describes the evolving trajectories of CO2 emissions from 2005 to 2017 of 2004 EU accession members by providing detailed emission inventories by 28 types of energy and 47 socioeconomic sectors. We further quantify the contributions of four socioeconomic drivers (i.e., economic growth, energy structure, carbon intensity, and energy intensity) to the emission changes. The results show that the total CO2 emissions of the ten countries decreased by 7.50% from 2010 (506.81 Mt) to 2016 (468.78 Mt), which is lower than the average decline rate of other EU members (10.52%). Although the effect of economic growth contributed the most to emission increase (15.44%), it is completely offset by the decline in carbon intensity (-18.82%). We also discuss potential roadmaps towards carbon neutrality by designing 33 scenarios based on the European Union Low-Carbon Development Map 2050. We find that carbon neutrality cannot be achieved unless the share of renewable energy sources reaches 60% and more than half of existing coal and gas power plants are upgraded to Carbon Capture Storage (CCS) technology. These changes require the implementation of both short-term and long-term strategies.